(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper the range of (x,t) for the corresponding u involved in Burger’s equation is obtained. The used methodology is C-R equation along with conditions u_x=v_t, u_t=-v_x. When approached through this method easily we can solve v for the given u and u for the given v simultaneously without loss of generality.